Collision tumor of ovary: A rare entity - Karki, Diksha; Karki, Smriti; Adhikari, Purbesh; Dahal, Mona; Adhikari, Milan; Adhikari, Bindu (Asian Journal of Medical Sciences, 2018)
Collision tumors are composed of two histologically distinct neoplasms in the same organ without intermixture of cell types. The co-occurrence of a serous adenocarcinoma with a mature cystic teratoma is very rare. We present here the case of a 48 years married female with bilateral high grade serous carcinoma of the ovary with left sided mature cystic teratoma. Asian Journal of Medical Sciences Vol.9(4) 2018 61-64